The effect of an a2d calcium channel blocker on sleep parameters in women with chronic primary insomnia: a pragmatic study - Ebrahim, Naseem (My University, 2014)
Chronic neuropathic pain, epilepsy, depression and anxiety disorders have been treated successfully with pregabalin. Normal subjects, epileptics and patients with neuropathic pain to whom pregabalin was prescribed showed an improvement in objective and subjective sleep parameters. To determine if pregabalin’s sleep enhancing effect is an independent process, it is necessary to test pregabalin in primary insomniacs who do not have conditions that could be treated by pregabalin. My study was designed as a double blind, randomised, crossover, placebo controlled trial, with 50 milligrams of pregabalin or placebo was administered for eight consecutive nights. I performed polysomnographic recordings on eight female chronic primary insomniacs on five nights. Sleep recordings were performed prior to the intervention, and on the first night and eighth night of each treatment. Subjects filled out subjective scales at baseline and night eight of every treatment. While polysomnography and subjective scales showed that my subjects were insomniac, sleep variables during the pregabalin or placebo period were unchanged when compared to baseline. A daily dose of 50 mg pregabalin did not have any significant effects on either sleep architecture or subjective sleep variables in female chronic primary insomniacs.
Keywords: Insomnia.; Sleep disorders.; Calcium antagonists.